2006
DOI: 10.1128/iai.00293-06
|View full text |Cite
|
Sign up to set email alerts
|

Opacity-Associated Adhesin Repertoire in Hyperinvasive Neisseria meningitidis

Abstract: The opacity (Opa) proteins mediate a variety of interactions between the bacterium Neisseria meningitidis and its human host. These interactions are thought to be of central importance in both the asymptomatic colonization of the nasopharynx and the sporadic occurrence of meningococcal disease. The receptor specificities of a limited number of Opa protein variants have been explored, but the high level of amino acid sequence diversity among variants has complicated the assignment of specific roles to individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 61 publications
(80 reference statements)
4
51
0
6
Order By: Relevance
“…Meningococcal isolates of the same MLST ST or clonal complex that were recovered over several decades still show considerable similarities in their opa allelic profiles (10,19), with retention of the same allele in one clonal complex over more than 50 years and, in two clonal complexes, of the same opa allelic profile in isolates recovered 25 years apart (10). The sets of meningococcal isolates studied by Callaghan et al are much more distantly related than the sets of gonococcal isolates used in this study, as the former are defined by having the same or similar allelic profiles by MLST, which indexes variation in housekeeping genes that evolve slowly, whereas the latter are defined by identity of antigen genes, which evolve very much more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Meningococcal isolates of the same MLST ST or clonal complex that were recovered over several decades still show considerable similarities in their opa allelic profiles (10,19), with retention of the same allele in one clonal complex over more than 50 years and, in two clonal complexes, of the same opa allelic profile in isolates recovered 25 years apart (10). The sets of meningococcal isolates studied by Callaghan et al are much more distantly related than the sets of gonococcal isolates used in this study, as the former are defined by having the same or similar allelic profiles by MLST, which indexes variation in housekeeping genes that evolve slowly, whereas the latter are defined by identity of antigen genes, which evolve very much more rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified combinations of Opa proteins consistently observed in meningococcal hyperinvasive clonal complexes over decades of epidemic spread (5,27). Hyperinvasive clonal complexes are not representative of the genetic diversity observed in asymptomatically carried meningococcal populations, however, which are composed of numerous, diverse genotypes (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Populationbased studies of Opa diversity have suggested that the meningococcal hyperinvasive clonal complexes, genotypes identified by multilocus sequence typing (MLST) and responsible for the majority of global meningococcal disease (14,20), are associated with particular Opa repertoires (5,27). It is unclear whether this association is unique to disease-causing meningococci or whether clonal complexes isolated from asymptomatic carriage that have never or rarely caused disease also exhibit this feature.…”
mentioning
confidence: 96%
See 2 more Smart Citations